EFEKTIVITAS PENYELENGGARAAN PROGRAM BANTUAN BIAYA PENDIDIKAN BIDIKMISI DI UNIVERSITAS RIAU - Adi Kurniawan; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Government through the Directorate General for Education and Student Affairs, Ministry of Research, Technology and Higher Education began in 2010 launched the Assistance Program Tuition Fee Bidikmisi ie tuition assistance for students finish their studies and have academic potential both for education at college of the excellent courses until graduation and timely. Riau University is one of the Universities that receive Tuition Fee Assistance Program Bidikmisi with the number of recipients as much as 4338 students from 2010 to 2016 today. But at the University of Riau are still many problems, especially in its implementation are: Beneficiary Assistance Program Tuition Fee Bidikmisi in Riau University not only come from poor families in economic terms alone, but the middle class and above are also many who enjoy this assistance program, the number of IPK low, the number who passed was not timely, and the number of recipients Tuition fee Assistance Program Bidikmisi who complained about delays in disbursement of founds. This study aims to determine the Effectiveness of the Implementation of Tuition Assistance Program Bidikmisi at the University of Riau. The concept of the theory used is the effectiveness of the theory, advanced by Mahmudi in his book entitled Public Sector Performance Management. This study used a qualitative descriptive approach using purposive sampling method with data collection using interviews, observation, and documentation. The results of this study is the Tuition Fee Assistance Program Implementation Bidikmisi at the University of Riau yet effectively held fully. It can be seen from the goals and objectives of the program are not yet fully materialized as expected in government who. Factors affecting among other things: Goals and Objectives Program, Human Resources. Which all of these factors are very influential for the achievement of Effectiveness of the Implementation of Tuition Assistance Program Bidikmisi at the University of Riau.Keywords: Effectiveness, Implementation, Bidikmisi.